2017
DOI: 10.1111/tri.12996
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biliary anastomotic stricture after deceased donor liver transplantation: the impact of platelet counts - a retrospective study

Abstract: Biliary stricture is a common cause of morbidity after liver transplantation (LT). This study aimed to determine the risk factors for post-transplant biliary anastomotic strictures (BAS), focusing on perioperative platelet counts. We enrolled 771 consecutive recipients who underwent ABO-identical/compatible deceased donor LT with duct-to-duct biliary reconstruction from January 2000 to June 2012. BAS was identified in 142 cases. The median time for stricture development was 176 days. Preoperative and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Another question may arise as to why low platelet count on POD 5 has an influence on long‐term outcomes. In our preliminary study, we found that low platelet count on POD 5 was strongly related with biliary anastomotic strictures, which developed as a late complication . Biliary complications are associated with infectious complications, readmission, and multiple radiological, endoscopic or surgical interventions .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another question may arise as to why low platelet count on POD 5 has an influence on long‐term outcomes. In our preliminary study, we found that low platelet count on POD 5 was strongly related with biliary anastomotic strictures, which developed as a late complication . Biliary complications are associated with infectious complications, readmission, and multiple radiological, endoscopic or surgical interventions .…”
Section: Discussionmentioning
confidence: 88%
“…In our preliminary study, we found that low platelet count on POD 5 was strongly related with biliary anastomotic strictures, which developed as a late complication. 21 Biliary complications are associated with infectious complications, readmission, and multiple radiological, endoscopic or surgical interventions. 22 It is presumed that Our results suggest that maintaining platelet counts ≥72 500/μL on POD 5 could potentially improve graft and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results are in line with the “60-5 criterion”, although the cutoff point was different. In fact, another study[29] validating the “60-5 criterion” also identified a cutoff point different from the one originally proposed. At the time of transplantation, patients with a lower PC on 5POD had a more severe disease: The mean MELD was higher (16.8 ± 5.4 vs 15.7 ± 5.0; P = 0.033), and most of them were in the C category of the CTP score (30.4% vs 23.6%, P = 0.014), which could predict the onset of intra- and postoperative complications.…”
Section: Discussionmentioning
confidence: 95%
“…Takahashi et al[ 29 ] focused on the long term impact after DDLT and noted that a platelet count of < 72.5 × 10 3 /μL on POD 5 was a predictor for poor graft and patient survival. More recently, Takahashi et al[ 30 ] described that low perioperative platelet counts within 5 d after DDLT were associated with biliary anastomotic stricture (BAS) with duct-to-duct biliary reconstruction. They found that persistent postoperative thrombocytopenia, which was defined as platelet counts of < 41 × 10 3 /μL and < 53 × 10 3 /μL on POD 3 and POD 5, respectively, was an independent risk factor for BAS.…”
Section: Platelets and Ddltmentioning
confidence: 99%
“…Clinical studies suggest that increasing postoperative platelet counts might improve graft and patient survival after DDLT[ 28 - 30 ]. This “protective effect of platelets” may be compatible with a study by Hisakura et al[ 33 ] who showed that thrombopoietin-mediated thrombocytosis protected the liver from damage after an extended hepatectomy in a pig model.…”
Section: Platelets and Ddltmentioning
confidence: 99%